The “great flood” of 1926: Environmental change and post-disaster management in British Malaya - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2016)
This paper is an historical case study of a major flood that occurred in British Malaya in 1926. It focuses on two key points. First, that the magnitude and subsequent impacts of the flood were exacerbated by contemporary industrial, agricultural, and hydraulic practices. Second, that this event pushed the British colonial government toward improving their land and river management strategies over the following decades. This article draws on recent research arguing the importance of an historical approach to disaster, as it enables greater insight into a disaster's causes and long‐term political, social, and environmental ramifications. Focussing on December 1926—a month of especially severe flooding likely linked to La Niña—this article will explore how those inundations became disastrous because of man‐made changes enacted on the local environment. It will consider the sequential effect of the inundations, from their immediate to medium‐term impact on the environment, to subsequent government‐led flood mitigation schemes. By viewing the mid‐1920s floods as a catalyst for change, with the benefit of hindsight, it is also possible to assess how far these changes were positive or negative.